(untitled) (Bangladesh Journal of Bioethics, 2015)
Heartiest Eid Mubarak to all our readers, authors and well wishers! This issue of the Bangladesh Journal of Bioethics has a unique combination of papers focusing on rights human and animal. The papers search deeply into the ethical issues related to scientific research and raises pertinent questions. Another critical topic addressed is the mutually beneficial relationship between the pharmaceutical industry and the physicians and possible impact on the services to patient. All the papers are important and highly relevant to the principles of Bioethics. Bangladesh Journal of Bioethics 2015 Vol.6 (1):